A study of causes that affects the employee relation in Cyberview Resort & Spa / Nur Shaffila Muhamad Asri - Muhamad Asri, Nur Shaffila (Faculty of Business and Management, 2012)
The impact of employee relation has received considerable attention by senior management, human resources professionals, and industrial psychologists. It has been proven to be one of the most essential element intractable human resource challenges confronting organizations. The purpose of this study is to examine the factor that influencing effectiveness of employee relation in Cyberview Resort & Spa. The main aim of this study is to identify and determine the relationship between communication, management role, associate role and employe recognition program with employee relation. This study was focused on to all staff at all departments their total staffs are 120. This study was using questionnaire as data collection method which is the respondent has been chosen through simple random sampling. As the results, all objectives were achieved and have significant relationships with employee relation. The manager needs to focus on the most influential factor which is communication, it can be done by organize monthly meeting which attend by all department representative and monthly gathering emphasize on casual tea time due to encourage informal conversation among top and lower management. By doing this event it will encourage the employee to participate in resolving the matter. In addition, provide a proper communication medium such as notice board each department in the resort also important due to make sure the flow of information run smoothly. Lastly, voting system should be implementing in recognition program to avoid bias and negative situation occurs. So both sides should give full cooperation in order to improve employee relation in the organization due to employee relation is a reciprocal behavior between employer and employee.